Smartphone Digital Applications for Heart Failure Surveillance: A Scoping Review - Yudi Purnomo; Yanny Trisyani; Aan Nuraeni (Universitas Aisyah Pringsewu, 2023)
Background: Developments in the information and digital technology sector have provided a solid foundation for the emergence of smartphones. Heart failure is very important to monitor. Given this, a remote monitoring strategy involves smartphones. Objective: to get an overview of digital applications smartphones or m-Health, which allows independent monitoring and remote surveillance of self-care heart failure patients. Method: The methodology for this review follows the JBI coverage review methodology. Several searches were made databases: Pubmed, CINAHL, Scopus, and ScienceDirect. The PRISMA-ScR conceptual framework was followed for data extraction and categorization purposes. Results: 15 studies were included, screened and assessed for inclusion by two independent reviewers involving 8273 patients from 7 different countries. All studies were analyzed as part of this review, facilitating digital application smartphones for self-care heart failure management. 1 study applied fluid measurement, four studies applied NT pro-BNP level measurement, and 1 study used bilingual. Five studies reviewed patient satisfaction levels, two studies reviewed staff satisfaction, and four studies reported LVEF data. Conclusion: This review shows that the use of digital applications is based on smartphones can improve self-care management, quality of life, readmission event monitoring, health literacy, monitoring of symptoms, blood pressure, monitoring of NT-Pro BNP levels, monitoring of depressive symptoms, reporting of LVEF results, with positive feedback, good medical results, and satisfaction with the application of this application from patients and staff can be an integral part of the management of heart failure. Abstrak: Latar Belakang: Perkembangan di sektor informasi dan teknologi digital telah memberikan dasar yang kuat untuk smartphone kemunculannya. Gagal jantung sangat penting untuk dipantau. Mengingat hal ini, strategi pemantauan jarak jauh yang melibatkan smartphone. TUJUAN: Untuk mendapatkan gambaran umum smartphone aplikasi digital atau M-Health, yang memungkinkan pemantauan independen dan pengawasan jarak jauh dari pasien kegagalan sendiri. Metode: Metodologi untuk ulasan ini mengikuti metodologi ulasan cakupan JBI. Beberapa pencarian dilakukan basis data: PubMed, Cinahl, Scopus, dan ScienceDirect. Kerangka kerja konseptual PRISMA-SCR diikuti untuk tujuan ekstraksi dan kategorisasi data. Hasil: 15 studi dimasukkan, disaring dan dinilai untuk dimasukkan oleh 2 pengulas independen yang melibatkan 8273 pasien dari 7 negara yang berbeda. Semua studi dianalisis sebagai bagian dari ulasan ini, memfasilitasi smartphone aplikasi digital untuk manajemen gagal jantung perawatan diri. 1 Studi pengukuran cairan yang diterapkan, 4 studi menerapkan pengukuran tingkat NT-BNP, dan 1 penelitian menggunakan bilingual. 5 Studi meninjau tingkat kepuasan pasien, 2 studi meninjau kepuasan staf dan 4 studi melaporkan data LVEF. Kesimpulan: Ulasan ini menunjukkan bahwa penggunaan aplikasi digital didasarkan pada smartphone dapat meningkatkan manajemen perawatan diri, kualitas hidup, pemantauan peristiwa penerimaan kembali, melek kesehatan, pemantauan gejala, tekanan darah, pemantauan tingkat BNP-NT, pemantauan Gejala depresi, pelaporan hasil LVEF, dengan umpan balik positif, hasil medis yang baik, dan kepuasan dengan aplikasi aplikasi ini dari pasien dan staf dapat menjadi bagian integral dari manajemen gagal jantung.